2013
DOI: 10.1093/rheumatology/kes375
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of demyelination occurring during anti-TNF-α therapy: a French national survey

Abstract: Causal relationship between anti-TNF-α and induction of DD remains unclear, but in some cases the chronology of clinical events is suggestive. Nevertheless, DD might persist despite treatment discontinuation, suggesting that anti-TNF-α could trigger the demyelinating process, which further evolves independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 12 publications
5
91
1
5
Order By: Relevance
“…Although our data support the previous work implicating TNF-a as a key cytokine that can dramatically influence oligodendrocyte biology (Fig. 4), we know that anti-TNF-a therapies are not a clinically relevant reality in MS because they can exacerbate the disease and even initiate MS-like symptoms and diagnoses in other patient populations (28)(29)(30). Although the mechanisms remain unclear, TNF-a has two known receptors (TNFR1 and TNFR2) that have pleiotropic effects in the context of neurodegenerative diseases (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 86%
“…Although our data support the previous work implicating TNF-a as a key cytokine that can dramatically influence oligodendrocyte biology (Fig. 4), we know that anti-TNF-a therapies are not a clinically relevant reality in MS because they can exacerbate the disease and even initiate MS-like symptoms and diagnoses in other patient populations (28)(29)(30). Although the mechanisms remain unclear, TNF-a has two known receptors (TNFR1 and TNFR2) that have pleiotropic effects in the context of neurodegenerative diseases (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 86%
“…Our cases, as well as others [18], clearly support discontinuation of any type of anti-TNFα treatment. If the patient does not fulfill the criteria for MS (clinically isolated symptom with atypical demyelination), we believe that MS treatment should be withheld and that clinical/MRI follow-up at 6-month or 1-year intervals may suffice.…”
Section: Discussionsupporting
confidence: 87%
“…Despite initial experimental data supporting a potentially therapeutic effect of anti-TNFα treatment on autoimmune demyelination [15], clinical data revealed that anti-TNFα drugs can potentially exacerbate a latent MS or induce atypical CNS demyelination [2,14,16]. Specifically in AS, single cases [7,17] as well as recent large cohorts [18] report sequential development of typical MS or CNS demyelination (such as optic neuritis or myelitis) after anti-TNFα treatment. In our cases, similar treatment resulted in either exacerbation of an already diagnosed MS (case 1), or in de novo development of neurological symptoms and brain MRI lesions in cases 3-5; the presence of MS in case 2 discouraged the treating rheumatologist from prescribing an anti-TNFα regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Demyelinating CNS and PNS disorders, following treatment with anti-TNF agents, have been described in many clinical studies and case series [190][191][192][193][194][195]. However, contradictory reports do exist; a prospective study in patients who had undergone neurological examination and neuroimaging studies before anti-TNF treatment initiation showed that the frequency of demyelination due to anti-TNF treatment is rather low [196].…”
Section: Cns and Pns Demyelination Caused By Anti-tnf Agentsmentioning
confidence: 99%